Effect of increase in load and frequency on the resilience of railway ballast. Issue 9 (15th October 2018) - Sun, Qideng; Indraratna, Buddhima; Ngo, Ngoc Trung
Abstract : This paper presents the results of a series of large-scale cyclic triaxial tests conducted on ballast subjected to increased load and frequency of loading. For a given loading, the laboratory test data demonstrate that the resilient modulus of ballast is influenced by the frequency of loading. Both strain hardening and strain softening can be observed in response to increasing magnitude of load and frequency. A correlation between the resilient modulus and bulk stress is introduced to describe both the strain-hardening and strain-softening behaviour of ballast under different frequencies. A good corroboration between the cyclic stress ratio and the accumulated permanent strain and the resilient strain is demonstrated.